Effect of secukinumab on the different GRAPPA-OMERACT core domains in psoriatic arthritis: a pooled analysis of 2049 patients - Orbai, A-M; McInnes, IB; Coates, LC; Husni, ME; Gladman, DD; Gossec, L; Pricop, L; Chambenoit, O; Meng, X; Mease, PJ (Journal of Rheumatology, 2019)
Objective. To compare the efficacy of secukinumab with that of placebo across the updated Group for Research and Assessment of Psoriasis and Psoriatic Arthritis and Outcome Measures in Rheumatology (GRAPPA-OMERACT) individual psoriatic arthritis (PsA) core domains using pooled data from 4 phase III PsA studies and 1 phase III ankylosing spondylitis (AS) study.